HISTOPATHOLOGICAL AND IMMUNOHISTOCHEMICAL STUDIES FOR THE PATHOGENESIS OF A LOW PATHOGENICITY H9 AVIAN INFLUENZA VIRUS IN EXPERIMENTALLY INFECTED COMMERCIAL BROILERS - R. Aslam; A. Aslam; Y. Tipu; J. Nazir; A. Ghafoor; S. Fatima (Journal of Animal and Plant Sciences, 2015)
Present study has been designed to check the pathological effects of a low pathogenicity H9 avian influenza virus on broilers following experimental infection through intranasal, ocular and oral route at 21 days of age. Moderate clinical signs were observed which started appearing at two days post infection (PI), became severe on five days while started subsiding from seven days onwards. Severity of the signs and lesions was highest in respiratory organs following intranasal route of infection. No mortality was observed except one bird each in the groups infected through intranasal and oral route of infection. Histopathology of the organs in the birds infected through intranasal route revealed severe hyperemic trachea and congested lungs. While moderate congestion of kidneys and mild necrosis in the liver tissue was seen in all treatment groups. Detection of virus antigen through immunohistochemistry was possible in trachea, lung, and kidney of few birds on two days PI while in all birds at five days PI. In some of the birds inoculated through either of the route, the virus was detected in liver and duodenum tissue at five days PI.
Keywords: H9; AIV; IHC staining; Histopathology; Postmortem